Optimal cell-to-cell active balancing using fuzzy type-2 BEC implemented zeta and quasi-resonant buck converters on Li-ion based battery pack - Sudiharto, Indhana; Murdianto, Farid Dwi; Widyasavitta, Vena Chika (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Many motorized vehicles use non-environmentally friendly fuels causing more pollution. To tackle this, electric vehicles with battery technology are becoming popular. Many electric cars use Li-ion battery packs. However, these battery packs can have differences between individual batteries, affecting their performance. When electric cars accelerate, the batteries can get imbalanced, which shortens their lifespan. To prevent this, a balancing circuit is needed to make sure each battery cell stays equal. To get the balancing current according to the needs of each battery cell and switching network components. As a result, this research creates a cell-to-cell active balancing using the quasi-resonant buck converter that can reduce ripple from zeta converter output. Fuzzy type-2-BEC adjusts the duty cycle zeta converter circuits. The output is set equal to the average cell voltage. Four pieces of Li-ion are connected in the series at 14.4 V/3 Ah. To test the balancers, two variations were used to determine the system's reliability. From the test result, variation one can balance all cells at the 60 s, and variation two can balance all cells at the 150 s.